2014
DOI: 10.1194/jlr.r046599
|View full text |Cite
|
Sign up to set email alerts
|

Ketone body therapy: from the ketogenic diet to the oral administration of ketone ester

Abstract: This article is available online at http://www.jlr.org family, its importance for purposes of this review is minimal.). KBs have been dubbed "metabolism's ugly duckling" because, in the mid-19th century, they were fi rst discovered in large quantities in the urine of patients succumbing to diabetic ketoacidosis. Thus, it is not surprising that physicians of the era considered KBs to be toxic byproducts of impaired carbohydrate metabolism. It took almost half a century for medical scientists to understand that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
109
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(111 citation statements)
references
References 79 publications
2
109
0
Order By: Relevance
“…284 In addition, keeping in view the significant role of inflammation and metabolic alteration, a ketogenic diet also provides an efficient therapeutic strategy, because lowering lactate production by ketogenic diet has been shown to decrease MDSC frequency leading to improved antitumour immune response.285 Remarkably, a ketogenic diet causes minimal side effects as previously demonstrated that a 2-7 mM ketone body concentration can be achieved without giving rise to clinical acidosis. 286 Recalling the fact that, at the time of diagnosis around 80% of patients with PDAC present cachexia, ketogenic diet might serve as an anti-cachectic agent as well as an anti-cancer agent. [284][285][286] …”
Section: Diet and Dietary Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…284 In addition, keeping in view the significant role of inflammation and metabolic alteration, a ketogenic diet also provides an efficient therapeutic strategy, because lowering lactate production by ketogenic diet has been shown to decrease MDSC frequency leading to improved antitumour immune response.285 Remarkably, a ketogenic diet causes minimal side effects as previously demonstrated that a 2-7 mM ketone body concentration can be achieved without giving rise to clinical acidosis. 286 Recalling the fact that, at the time of diagnosis around 80% of patients with PDAC present cachexia, ketogenic diet might serve as an anti-cachectic agent as well as an anti-cancer agent. [284][285][286] …”
Section: Diet and Dietary Interventionsmentioning
confidence: 99%
“…286 Recalling the fact that, at the time of diagnosis around 80% of patients with PDAC present cachexia, ketogenic diet might serve as an anti-cachectic agent as well as an anti-cancer agent. [284][285][286] …”
Section: Diet and Dietary Interventionsmentioning
confidence: 99%
“…[25] The other studies described that ketone bodies supplements, ketone monoester (KME), have protective effects in the brain by potentiating the KD and prevention of glucose consumption in brain cells. [41,42] The mechanism of bHB inhibiting oxidative stress has mentioned in some studies. The ketone body bHB increased the global histone acetylation in mouse model caused changes in transcription genes encoding oxidative stress resistance factors FOXO3A and MT2.…”
Section: Ketogenic Diet As An Adjuvant Therapymentioning
confidence: 99%
“…[45] Interesting data uncovered the role of bHB in reducing the growth of glioblastoma cells in the presence of glucose in some cancer cell lines and increasing the radio-sensitivity in vitro studies. [41] Moreover, the efficacy of chemotherapy drugs has been increased by ketone bodies in vitro.…”
Section: Ketogenic Diet As An Adjuvant Therapymentioning
confidence: 99%
“…It is unclear to what extent such differences affect the variables measured, but it is not unlikely that the amount of carbohydrate in the diets can considerably affect the degree of ketonemia and/or glycemia and thereby the experimental results. A strict hyperketogenic diet as prescribed for control of refractory epilepsy in humans can result in blood ketone levels of up to 12 mmol/L [51], whereas more moderate ketogenic diets with higher protein and/or carbohydrate content typically result in ketonemia around 4-6 mmol/L (reviewed in [52]). …”
Section: Brain Ketone Metabolismmentioning
confidence: 99%